2015
DOI: 10.18869/modares.jcp.5.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Mass rearing of Bracon hebetor (Hym.: Braconidae) on wax moth, Galleria mellonella (Lep.: Pyralidae) with varying density of parasitoid and the host

Abstract: Rearing methods for Bracon hebetor (Say) (Hym., Braconidae) were investigated in the series of laboratory experiments designed to enhance the yield of the mass rearing of this parasitoid for biological control of lepidopteran field and stored product pests. In these experiments, the effects of parasitoid and host densities on fertility and sex ratio of B. hebetor were assessed. In parasitoid densities, 50 last-instar greater wax moth (GWM) Galleria mellonella (L.) larvae were placed per container and 1, 2, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Egg dispersion by H. hebetor on larvae of P. interpunctella has been shown to decrease as the host density increased [43]. In a study by Rotary and Gerling, a high host parasitoid ratio increased the percentage egg hatch and adult emergence by H. hebetor when reared on G. mellonella [45]. In a study by Ghimire and Phillips, progeny numbers of H. hebetor parasitizing late instars of P. interpunctella were higher at high host densities compared to lower densities [44].…”
Section: Factors Influencing Host Parasitism and Reproductive Effimentioning
confidence: 99%
See 1 more Smart Citation
“…Egg dispersion by H. hebetor on larvae of P. interpunctella has been shown to decrease as the host density increased [43]. In a study by Rotary and Gerling, a high host parasitoid ratio increased the percentage egg hatch and adult emergence by H. hebetor when reared on G. mellonella [45]. In a study by Ghimire and Phillips, progeny numbers of H. hebetor parasitizing late instars of P. interpunctella were higher at high host densities compared to lower densities [44].…”
Section: Factors Influencing Host Parasitism and Reproductive Effimentioning
confidence: 99%
“…In a study by Ghimire and Phillips, progeny numbers of H. hebetor parasitizing late instars of P. interpunctella were higher at high host densities compared to lower densities [44]. The influence of host density on the sex ratio of H. hebetor has also been investigated [44,45,46,47]. A previous study showed that the offspring sex ratio (male/total) increased with decreasing host/parasitoid ratio [47].…”
Section: Factors Influencing Host Parasitism and Reproductive Effimentioning
confidence: 99%
“…and Apanteles galleriae (Wilkinson) (Hymenoptera: Braconidae), are potential biocontrol agents to wax moths (Kwadha et al 2017). A. galleriae causes disturbance in development and alterations in the endocrine system of GWM larvae (Wanl et al 1994), while the venom of B. hebetor showed negative effects on GWM reducing oxygen consumption of larvae (Waller 1965), meanwhile GWM can be used for mass rearing of B. hebetor (Alam et al 2015). In fact, these two parasitoids attack wax moth larvae in stored combs outside hives or inside empty hives.…”
Section: Parasitoidsmentioning
confidence: 99%
“…B. hebetor is considered one of the best potential biological control agents for stored-product insects in the family Pyralidae (Brower et al 1996). B. hebetor females paralyze their hosts, which are typically last-stage larvae in a "wandering" phase, by stinging them, injecting paralytic venom, and ovipositing variable numbers of eggs on or near the surface of paralyzed hosts (Alam et al 2015).…”
Section: Introductionmentioning
confidence: 99%